Uczeń gimnazjum: wykreowana tożsamość „pomiędzy” - Magdalena Cuprjak, Magdalena Cuprjak (Studia Edukacyjne, 2020)
This article presents a part of a study conducted in the middle school in a small town in the Region of Kujawsko-Pomorskie, interviews and drawing projections of students in one class. Analyses concern two categories: perceptions of the middle school as reported by the students and the new quality of the so-called “in-between” identity. This is an identity created by the specific context that simulated adulthood – a school “suspended” between the two worlds of childhood and adulthood.